Riding the Wave: Spirituality, Creative Expression, and Adult Learning - Randee Lipson Lawrence; Soni Simpson (Adult Education Research Conference, 2008)
This paper explores the relationship between creative expression and spirituality, examining ways in which adults seek knowledge and/or make meaning through these connections. Four themes emerged from this research: trust and letting go of control, a sense of connectedness, flow and devotion, and creativity as a healing force.
Keywords: creativity; spirituality; arts-based learning